Penser l'histoire religieuse au XXIe siècle - Krumenacker, Yves; Mentzer, Raymond A. (Chrétiens et Sociétés. Documents et Mémoires, 2020)
History today is very fragmented, each sector having its own traditions, its own historiography, its own references. Religious history is obviously no exception. But the worst thing would be for the different historical specialisations to ignore each other, even though they have much to learn from each other. This question was at the heart of the colloquium of the International Commission for the History and Study of Christianity, held in Lyon from 11 to 13 June 2019. Historians from a dozen different countries sought to show how other historical disciplines, such as the history of the present, transnational and global history, economic history, the history of the book, the history of justice, digital history, the history of knowledge, and the history of gender, with their own contributions and methodology, can enrich religious history. They have also shown the interest of confronting different national historiographical traditions. This book is the result, with chapters that are both methodological reflections and case studies from the sixteenth to the twenty-first centuries in Catholic, Protestant and Orthodox countries. It hopes to contribute to a reflection on how religious history can be done in the twenty-first century. The contributions to this volume were brought together by Yves Krumenacker, Professor of Modern History at the University of Lyon (Jean Moulin) and by Raymond A. Mentzer, professor of religious history at the University of Iowa (Daniel J. Krumm Family Chair in Reformation Studies).